Learning Through Projects: A Path to Better Student Collaboration - Alonemarera, A. S.; Mardin, Herinda (Universitas Sembilanbelas November Kolaka, 2025)
Collaboration skills are one of the 21st-century skills that are very important for students, especially in facing the challenges of the complex world of work and social life. Students' collaboration skills in the Biology Education Study Program at Universitas Sembilanbelas November (USN), Kolaka, are still relatively low. One approach believed to improve students' collaboration skills is the application of Project-Based Learning (PjBL). Thus, this study aims to determine the effect of the application of Project-Based Learning on the collaboration skills of students in the Biology Education Study Program at USN Kolaka. This study is a pre-experimental type using a one-group pretest-posttest design. The subjects of the study were all active students (16 people) of the biology education study program, even the semester of the 2024/2025 academic year, who took the course